Bridging Music Informatics with Music Cognition - Frank A. Russo (Frontiers Research Topics, 2018)
Music informatics is an interdisciplinary research area that encompasses data driven approaches to the analysis, generation, and retrieval of music. In the era of big data, two goals weigh heavily on many research agendas in this area: (a) the identification of better features and (b) the acquisition of better training data. To this end, researchers have started to incorporate findings and methods from music cognition, a related but historically distinct research area that is concerned with elucidating the underlying mental processes involved in music-related behavior.